ANALISIS TINGKAT KEPUASAN PENGGUNA APLIKASI GRAB KOTA LUBUKLINGGAU MENGGUNAKAN FRAMEWORK PIECES - Cindi Wulandari; Elmayati Elmayati; Yulia Citra (Jurnal Teknologi Informasi Mura, 2020)
The problem in this study was how consument satisfy level on Grab Application in Lubuklinggau based on consument perception measured by framework PIECES (Performance, Information, Economic, Control, Efficiency, and Service). This study used collecting data method, by observation and record the research place, interview to interviewees and distribute the questionaires to the Grab service consument. The population in this study was all the Grab Application consument, it was 91 consument as the sample callculated by Slovin formula. The goal of this study was to know consument satisfy level on Information Technology Grab Application in Lubuklinggau, which measures by PIECES framework. The study result show that from validitas and reliability test all of the questionaires item were valid and reliable for multiple linier regretion test show that 6 (variable) have significant effect on consument satisty level except in economic variable. Keywords: Consument satisfy, Information Technology, PIECES